2019
DOI: 10.7150/thno.29987
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic MSH6-CXCR4-TGFB1 Feedback Loop: A Novel Therapeutic Target of Photothermal Therapy in Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) has been considered the most aggressive glioma type. Temozolomide (TMZ) is the main first-line chemotherapeutic agent for GBM. Decreased mutS homolog 6 (MSH6) expression is clinically recognized as one of the principal reasons for GBM resistance to TMZ. However, the specific functions of MSH6 in GBM, in addition to its role in mismatch repair, remain unknown. Methods: Bioinformatics were employed to analyze MSH6 mRNA and protein levels in GBM clinical sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…Interestingly, in other aggressive human tumors, such as melanoma and glioblastoma, TGFβ signaling is maintained in cancer cells, mainly through non-canonical signaling cascades (PI3K/AKT and RAS/MAPK pathways) 38 . In these tumors, canonical SMAD-dependent signaling also contributes to TGFβ pro-metastatic functions, particularly by upregulating genes involved in epithelial to mesenchymal transition, such as SLUG and SNAIL 39 , 40 . Here, we found that TGFBI signaling follows an alternative, non-canonical pathway that in some CRC cell lines relies on p38.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in other aggressive human tumors, such as melanoma and glioblastoma, TGFβ signaling is maintained in cancer cells, mainly through non-canonical signaling cascades (PI3K/AKT and RAS/MAPK pathways) 38 . In these tumors, canonical SMAD-dependent signaling also contributes to TGFβ pro-metastatic functions, particularly by upregulating genes involved in epithelial to mesenchymal transition, such as SLUG and SNAIL 39 , 40 . Here, we found that TGFBI signaling follows an alternative, non-canonical pathway that in some CRC cell lines relies on p38.…”
Section: Discussionmentioning
confidence: 99%
“…As a growth factor, TGF- β 1 exerts biological functions regulating cell proliferation, differentiation, apoptosis, and immunity. TGF- β 1 induces tumor cell apoptosis and inhibits tumor growth by regulating the downstream signal transduction molecule Smad in the early stages of tumor development [ 55 , 56 ]. With further development of the tumor, gene mutations in the TGF- β 1 receptor or its downstream Smad pathway accumulate in tumor cells, resulting in the weakening of TGF- β 1 inhibition [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the TGF- β 1 receptor promotes EMT, and polarized epithelial cells can be transformed into active stromal capable of invasion and migration. This process is a crucial stage of tumor occurrence, growth, and metastasis [ 56 , 57 ]. TGF- β 1 is a chemokine that can attract macrophages and fibroblasts and cause the release of bFGF, PDGF, TNF-a, and other vasoactive factors, thus promoting angiogenesis and inducing tumor metastasis [ 24 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…USI can also be evaluated systematically with multi-parameters such as Doppler and elastography (43). The ultrasound scan mode in this experiment included B-mode, CDFI, CPA and USE.…”
Section: Cvb-d Inhibition On the Growth Of Crc Xenograft Tumors In Numentioning
confidence: 99%